Enhancing Learning Quality through Management Support in Crafting Self-Assessment Questions at School - Zuhdi Zuhdi; Faridy Faridy; Hasan Baharun; Hefny Hefny; Ahmad Fauzi; M Aqil Fahmi (Al-Qalam Institute, 2024)
The research aims to evaluate the effectiveness of the management assistance approach in improving the quality of Independent Assessment questions at Madrasah Ibtidaiyah. The research methods will include a qualitative approach, participant observation techniques, in-depth interviews, and documentation. The data obtained will be analyzed thematically to identify patterns and themes in the process of preparing questions, as well as formulating relevant recommendations. The research results show that the management assistance approach in preparing Independent Assessment questions in Madrasah Ibtidaiyah in Besuk sub-district, Probolinggo district, has positively impacted the quality of the questions. Through this approach, teachers receive targeted guidance and direction to formulate questions more relevant to the curriculum and meet learning evaluation standards. In conclusion, the management assistance approach can effectively improve learning evaluation in Madrasah Ibtidaiyah in Besuk District. This research implies that applying a management assistance approach in preparing Independent Assessment questions can significantly improve the quality of learning evaluation at MI in Besuk District and similar educational institutions.